How chromosomal translocations arise to cause cancer: Gene proximity, trans-splicing, and DNA end joining - Patrick Streb; Eric Kowarz; Tamara Benz; Jennifer Reis; Rolf Marschalek (iScience, 2023)
Summary: Chromosomal translocations (CTs) are a genetic hallmark of cancer. They could be identified as recurrent genetic aberrations in hemato-malignancies and solid tumors. More than 40% of all “cancer genes” were identified in recurrent CTs. Most of these CTs result in the production of oncofusion proteins of which many have been studied over the past decades. They influence signaling pathways and/or alter gene expression. However, a precise mechanism for how these CTs arise and occur in a nearly identical fashion in individuals remains to be elucidated. Here, we performed experiments that explain the onset of CTs: (1) proximity of genes able to produce prematurely terminated transcripts, which lead to the production of (2) trans-spliced fusion RNAs, and finally, the induction of (3) DNA double-strand breaks which are subsequently repaired via EJ repair pathways. Under these conditions, balanced chromosomal translocations could be specifically induced. The implications of these findings will be discussed.